Phytochemical characterization, induction of apoptosis and activation of natural killer (nk) cells by abrus precatorius leaves extract on human breast cancer cell line - Ibrahim, Wan Suriyani Faliq Adeeba Wan (2020)
Cancer is still one of the global menace and poses a threat to the general world population. The search for cancer cure is also still on the race. Although conventional medicine remains the number one choice in cancer treatment, traditional approach is also still one of the favourable choices made by cancer patients to deal with this horrible disease. Traditional approaches, mainly by utilising medicinal plants are widely sought after in many countries since centuries ago. The ability of medicinal plants to exhibit their anti-proliferative activity, together with the ability to activate immune responses would be the ideal strategy to beat the disease. Therefore, understanding the mechanisms of medicinal plants displaying their anticancer properties scientifically would fill the gap of unknown knowledge about them. A medicinal plant known as Abrus precatorius or ‘saga’ were used in this study. This plant has been utilised traditionally to cure various ailments including cancer. The leaves of A. precatorius were selected to be extracted by different extraction techniques which employed different types of solvent. GC-MS was employed to provide the phytochemical analysis of the extracts. The ability of those extract to inhibit proliferation in cancer cells were measured using MTT assay. The best extract exhibiting the lowest inhibitory concentration (IC50) on the selected cancer cell, was selected to determine the mechanisms of action in inducing the cell death. Cell cycle arrest analysis, apoptosis staining with AnnexinV/PI and quantification of the expression of p53, Bac, Bcl-2 and Caspase-3 proteins were used to determine themechanism of cell deaths. Finally, the ability of the extract to induce immune response by activating NK cells was determined in a co-culture experiment of the NK cells with the target cell, MDA-MB-231 cells. This was observed by the analysis of target cell deaths and quantification of the secretion of cytokines, interleukin-2 (IL-2) and interferon gamma (IFN-g); and the degranulation of the cytotoxic granules by quantifying the perforin (PRF-1) and granzyme B (GzmB). The results showed that the ethyl acetate and methanol extracts prepared using Soxhlet contained the highest phenolic and terpenoid compounds comparing to the other extracts. The methanol extract obtained by Soxhlet, APME (A. precatorius methanol extract), exhibited the lowest IC50 value on MDA-MB-231 cells. Further analysis by flow cytometry revealed APME induced cell death on MDA-MB-231 cells via apoptosis, through DNA arrest at G0/G1 cycle, coupled with an increase of p53, Bax and Caspase-3 expression and decrease of Bcl-2 expression. APME was also found to activate NK cells (from healthy donor) by causing NK cell cytotoxic activity via apoptosis in the target cells. Increased levels of INF-g and PRF-1 were also observed in this co-culture experiment. These findings reflect the ability of A. precatorius leaves extract to exhibit the antiproliferative effect on cancer cells and stimulatory effect on NK cells from the healthy donors. This might be due to the presence of various phytochemical compounds in the extract that might act synergistically.